Steve Paxton and Trisha Brown Falling in the Dynamite of the Tenth of a Second - Goldman, Danielle (Edinburgh: Edinburgh University Press, 2004)
RESUMEN: During the 1960s and 1970s, dancers experimented with weight, improvisation, and falling in unprecedented ways; perhaps one could even say they positioned themselves as Pollock's paint, exploring what it meant to be matter falling through space. As with Pollock, people were there to record it. In 1983, Steve Paxton, in conjunction with Nancy Stark Smith, Lisa Nelson, and videographer Steve Christiansen, made Fall After Newton, a videotape tracing eleven consecutive years of contact improvisation, starting with Steve Paxton's Magnesium (1972) and ending with Contact's 11th Anniversary Concert Series at St Mark's Church, New York City. In this paper, I examine Fall After Newton, as well as Babette Mangolte's 1978 film of Trisha Brown's Water Motor, both documents of dancers who challenged modernism's obsession with verticality by experimenting with gravity. What interests me most about these two documents is their use of slow motion. Much in the way that Namuth, filming through glass, enabled viewers to see Pollock in new ways, Mangolte and Christiansen used slow motion to make visible dance that was impossible to see with the naked eye. Intrigued by the slowness made possible by technological means, this paper explores the significance of mechanically slowing down the fall of dancing bodies.